1995
DOI: 10.1021/jm00025a006
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N,N'-Substituted Piperazine and Homopiperazine Derivatives with Polyamine-like Actions at N-Methyl-D-aspartate Receptors

et al.

Abstract: A series of N,N'-substituted piperazine and homopiperazine derivatives have been synthesized with the objective of producing compounds that interact with polyamine modulatory sites on N-methyl-D-aspartate (NMDA) receptors. These novel compounds exhibited polyamine-like actions, enhancing [3H]MK-801 binding to NMDA receptors in rat forebrain membranes. The potencies of N,N'-bis(2-aminoacetyl)homopiperazine (15), N,N'-bis(N-methyl-4-aminobutyl)-piperazine (7), and N,N'-bis(3-aminopropyl)homopiperazine (11) (EC50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…Pharmacology. The regulatory effects of the diamines examined in this study were evaluated using [ 3 H]MK-801 binding since, under nonequilibrium conditions, this assay has been shown to be a sensitive and specific probe for effects at NMDA receptors. , Specifically, enhancement or inhibition of [ 3 H]MK-801 binding identifies substances that facilitate or reduce activity at the NMDA-gated calcium ion channel. ,− In overall agreement with the literature, , we found that in the nominal absence of glutamate and glycine (basal conditions) [ 3 H]MK-801 binding was enhanced by the addition of spermine. At an optimum concentration of 25 μM spermine, basal binding was increased between 350 and 1300%; basal binding decreased at higher concentrations of spermine.…”
Section: Resultssupporting
confidence: 80%
“…Pharmacology. The regulatory effects of the diamines examined in this study were evaluated using [ 3 H]MK-801 binding since, under nonequilibrium conditions, this assay has been shown to be a sensitive and specific probe for effects at NMDA receptors. , Specifically, enhancement or inhibition of [ 3 H]MK-801 binding identifies substances that facilitate or reduce activity at the NMDA-gated calcium ion channel. ,− In overall agreement with the literature, , we found that in the nominal absence of glutamate and glycine (basal conditions) [ 3 H]MK-801 binding was enhanced by the addition of spermine. At an optimum concentration of 25 μM spermine, basal binding was increased between 350 and 1300%; basal binding decreased at higher concentrations of spermine.…”
Section: Resultssupporting
confidence: 80%
“…The ground state geometry was calculated with all three versions of the Sparkle Model [22][23][24][25]. The calculations were carried out considering periodic bound conditions aiming to obtain a solid state structure [25].…”
Section: Structure Simulationmentioning
confidence: 99%
“…Sparkle/AM1 [22], Sparkle/PM3 [23] and Sparkle/PM6 [24] solid structure the X-ray diffraction simulations were performed. The structure obtained with the Sparkle/AM1 and PM6 models showed low level of agreement with the experimental result.…”
Section: Structure Simulation and Luminescence Spectroscopymentioning
confidence: 99%
“…Zhou et al reported N, N'disubstituted piperazine and homopiperazine derivatives with the objective of developing high-affinity polyamine site ligands that either facilitate or reduce activity at N-methyl-D-aspartate (NMDA) receptors. The homopiperazine compounds (26) showed polyamine-like actions by enhancing [ 3 H]MK-801 binding to NMDA receptors which are greater than compounds (27) [54]. The activation of NMDA receptors required for the induction of long-term potentiation in hippocampus, a process involved with learning and memory [55].…”
Section: 4-diazepine As Neuro Protective Agentsmentioning
confidence: 99%